Other cancers in lung cancer families are overwhelmingly smoking-related cancers. Issue 2 (27th June 2017) - Yu, Hongyao; Frank, Christoph; Hemminki, Akseli; Sundquist, Kristina; Hemminki, Kari
Familial risks of lung cancer are well-established, but whether lung cancer clusters with other discordant cancers is less certain, particularly beyond smoking-related sites, which may provide evidence on genetic contributions to lung cancer aetiology. We used a novel approach to search for familial associations in the Swedish Family-Cancer Database. This involved assessment of familial relative risk for cancer X in families with increasing numbers of lung cancer patients and, conversely, relative risks for lung cancer in families with increasing numbers of patients with cancers X. However, we lacked information on smoking. The total number of lung cancers in the database was 125 563. We applied stringent statistical criteria and found that seven discordant cancers were associated with lung cancer among family members, and six of these were known to be connected with smoking: oesophageal, upper aerodigestive tract, liver, cervical, kidney and urinary bladder cancers. A further novel finding was that cancer of unknown primary also associated with lung cancer. We also factored in histological evidence and found that anal and connective tissue cancers could be associated with lung cancer for reasons other than smoking. For endometrial and prostate cancers, suggestive negative associations with lung cancer were found. Although we lacked information on smoking it is prudent to conclude that practically all observed discordant associations of lung cancer were with cancers for which smoking is a risk factor. Among family members of lung cancer patients, 7 other cancers were found, all of which were smoking related http://ow.ly/ZLnt30csVfZ